Association between albuminuria and mortality in elderly subjects with diabetic foot seen in the outpatient clinic of the Peruvian Navy Medical Center (2010–2015) - Estremadoyro-Santillan, Héctor A. (2020)
Objective: to determine the relationship between albuminuria and mortality in elderly subjects with diabetic foot seen in the outpatient clinic in Cirujano Mayor Santiago Tavara Peruvian Navy Medical Center between 2010 and 2015. Materials and methods: this is a quantitative, observational, analytical and retrospective cohort study. Data from 89 elderly subjects who complied with selection criteria was entered. A descriptive analysis was performed in which the following variables were included: death during the study, comorbidities, and sociodemographic data. Afterwards, a bivariate analysis based on survival at the end of the study was performed, where all covariates based on the main variable of the study (mortality) were assessed. Results: average age of subjects was 79.3 ± 7.2 years, and they were mainly male (58.4%). We also found that 52 subjects (58.4%) had a past history of albuminuria, and that 7.9% of the studied population died during the study. All of them (100%) had albuminuria. Finally, as it was the case with albuminuria, all subjects who had undergone amputation because of diabetic foot died during follow-up. Conclusion: a significant relationship between albuminuria and mortality was found in elderly subjects with diabetic foot who were included in this study.